2021
DOI: 10.1371/journal.pone.0246460
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation among Bangladeshi children under-five years of age hospitalised for severe pneumonia: A randomised placebo controlled trial

Abstract: Introduction Vitamin D is important for its immunomodulatory role and there is an independent association between vitamin D deficiency and pneumonia. We assessed the effect of vitamin D supplementation on the outcome in children hospitalized for severe pneumonia. Methods This was a randomised, double blinded, placebo-controlled clinical trial in children aged >2–59 months with severe pneumonia attending Dhaka Hospital, icddr,b. Children received age-specific megadose of vitamin D3 (20,000IU: <6 months,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…We used the Cochrane risk of bias tool (2019 version) 7 to evaluate the qualities of the RCTs. Our overall risk of bias assessment showed low risk in 14 studies, 9 , 10 , 11 , 12 , 18 , 23 , 24 , 28 , 30 , 31 , 33 , 37 , 38 , 39 some concerns in 4 studies, 19 , 20 , 22 , 29 and high risk in 14 studies. 8 , 13 , 14 , 15 , 16 , 17 , 21 , 25 , 26 , 27 , 32 , 34 , 35 , 36 This assessment is provided in detail in eTable 2 in the Supplement .…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…We used the Cochrane risk of bias tool (2019 version) 7 to evaluate the qualities of the RCTs. Our overall risk of bias assessment showed low risk in 14 studies, 9 , 10 , 11 , 12 , 18 , 23 , 24 , 28 , 30 , 31 , 33 , 37 , 38 , 39 some concerns in 4 studies, 19 , 20 , 22 , 29 and high risk in 14 studies. 8 , 13 , 14 , 15 , 16 , 17 , 21 , 25 , 26 , 27 , 32 , 34 , 35 , 36 This assessment is provided in detail in eTable 2 in the Supplement .…”
Section: Resultsmentioning
confidence: 77%
“…The main search resulted in 2063 studies potentially relevant for inclusion ( Figure 1 ); of these, 32 studies 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 (8400 unique participants) met our criteria and were included in this systematic review ( Table 1 ). A subgroup of 21 studies 8 , 9 , 10 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 (7358 unique participants) were eligible for meta-analysis because they included a control group receiving either low-dose vitamin D supplementation (≤400 IU/d) or placebo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It would be reasonably advantageous to supplement only patients who may benefit the most, namely the ones with severe deficiency, and therefore, interventional studies should be planned targeting this group rather than those with any deficiency in order to define vitamin D dosage, mode of delivery as well as duration of supplementation. Interestingly, it should be pointed out that even in children with a sufficient serum vitamin D level at hospital admission, a lower trend for the duration of resolution of severe pneumonia in hours (72 (IQR:44–96) vs. 88 (IQR:48–132); p = 0.07) and duration of hospital stay in days (4 (IQR:3–5) vs. 5 (IQR:4–7); p = 0.09) was observed in a vitamin D group compared with placebo [ 49 ]. Evidence from previous observational studies and RCTs suggested that there may be health economic benefits in raising the vitamin D level in adults in Western Europe [ 50 ].…”
Section: Discussionmentioning
confidence: 99%